Diseño de una Nueva Alternativa De Aprovechamiento de Los Tiempos Libres En Los Recorridos En El Transporte Público De Bogotá. (2022)
Urban transport is one of the most important factors for the development of a population since it allows its users to access different elements of a company such as job opportunities, education, health, culture, and other environments that promote skills development; public transport also represents an essential factor for economic growth and represents an important determinant in local development.